Combined Nurr1 and Foxa2 roles in the therapy of Parkinson's disease. Issue 2 (February 2016) - Oh, Sang‐Min; Chang, Mi‐Yoon; Song, Jae‐Jin; Rhee, Yong‐Hee; Joe, Eun‐Hye; Lee, Hyun‐Seob; Yi, Sang‐Hoon; Lee, Sang‐Hun
Abstract :